เราได้ว่า E [ X 0 ] = X 0 = S {\displaystyle E[X_{0}]=X_{0}=S\,}
พิจารณา E [ X n | X n − 1 = c ] {\displaystyle E[X_{n}\ |\ X_{n-1}=c]\,} เราได้ว่า E [ X n | X n − 1 = c ] = 1 2 ⋅ 2 c + 1 2 ⋅ c 4 = 9 8 c {\displaystyle E[X_{n}\ |\ X_{n-1}=c]={\frac {1}{2}}\cdot 2c+{\frac {1}{2}}\cdot {\frac {c}{4}}={\frac {9}{8}}c\,}
ฉะนั้น จาก law of total expectation, E [ X n ] = ∑ c Pr ( X n − 1 = c ) E [ X n | X n − 1 = c ] = ∑ c Pr ( X n − 1 = c ) ⋅ 9 8 c = 9 8 ∑ c c Pr ( X n − 1 = c ) = 9 8 E [ X n − 1 ] {\displaystyle E[X_{n}]=\sum _{c}\Pr(X_{n-1}=c)E[X_{n}\ |\ X_{n-1}=c]=\sum _{c}\Pr(X_{n-1}=c)\cdot {\frac {9}{8}}c={\frac {9}{8}}\sum _{c}c\Pr(X_{n-1}=c)={\frac {9}{8}}E[X_{n-1}]}